Indikasi Sesar Naik di Plampang, Pulau Sumbawa Berdasarkan Analisis Gempa Bumi 13 Juni 2020 - Priyobudi; Ramdhan, Mohamad (EKSPLORIUM, 2021)
The existence of an active fault with a reverse fault mechanism in the Plampang area is successfully delineated from the distribution of the relocated hypocenter, the moment tensor inversion, and the Coulomb stress changes. This study also reveals the source of the earthquake in the active fault with a relatively shallow depth which can be a threat on Sumbawa Island if the maximum magnitude is released in the future. Seismicity from hypocenter relocation shows the distribution of the epicenter with a southwest–northeast direction. It is also supported by the moment tensor inversion result which shows the fault plane trending southwest–northeast (N2240E) with a steep dip (490). The vertical section of seismicity in the dip direction shows that the slope of the plane has a lower angle with increasing depth. The lower angle of a fault plane shows a decollement structure at a depth of 10–15 km and gradually becomes steep as a splay fault structure at a depth of 0–10 km. It is consistent with the result of moment tensor inversion which shows the mechanism of a reverse fault that occurred at a depth of 7 km. The Coulomb stress changes show the stress increasing outside the fault plane area, which triggers aftershocks. The distribution of aftershocks shows a hypothetical fault plane of 19 km long and 12 km wide. A fault of this size has the potential to generate an earthquake with a magnitude maximum of Mw 6.4. The Sumbawa earthquake on June 13, 2020, having M 5.3 was caused by a small part of the activity from the fault.